(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This paper presented the review of electrocardiogram and FPGA of digital filtrations.Electrocardiogram (ECG) signals are frequently distorted by electrical and mechanical noise includingpower line interference, electrode movement, motion artifacts, and so on. Doctors need a clear ECGsignal to make an accurate diagnosis. Filtering techniques to remove ECG signal noise using IIR FIRdigital filters have significant advantages over the former. Furthermore, a general-purpose multipliertakes up a lot of space on FPGAs, and its full flexibility isn’t always needed. Silicon devices could beprogrammed in the field to become almost any type of digital circuit or system. Faster time-to-marketand lower cost are two advantages of FPGAs over ASICs, which typically require a significant amount ofmoney and time to produce the first device.